Risk factors for Borna disease virus 1 encephalitis in Germany – a case–control study. Issue 1 (31st December 2023) - Pörtner, Kirsten; Wilking, Hendrik; Frank, Christina; Böhmer, Merle M.; Stark, Klaus; Tappe, Dennis
ABSTRACT: In 2018, Borna Disease Virus 1 (BoDV-1) was confirmed as a human zoonotic pathogen causing rare but fatal encephalitis in Germany. While diagnostic procedures and the clinical picture have been described, epidemiology remains mysterious. Though endemic areas and a natural reservoir host have been identified with the shrew Crocidura leucodon shedding virus in secretions, transmission events, routes and risk factors are unclear. We performed the first comprehensive epidemiological study, combining a large case series with the first case–control study: We interviewed family members of 20 PCR-confirmed BoDV-1 encephalitis cases deceased in 1996–2021 with a standardized questionnaire covering medical history, housing environment, profession, animal contacts, outdoor activities, travel, and nutrition. Cases' median age was 51 (range 11–79) years, 12/20 were female, and 18/20 lived in the federal state of Bavaria in Southeastern Germany. None had a known relevant pre-existing medical condition. None of the interviews yielded a transmission event such as direct shrew contact, but peridomestic shrew presence was confirmed in 13 cases supporting environmental transmission. Residency in rural areas endemic for animal BoDV-1 was the common denominator of all cases. A subsequent individually matched case–control study revealed residence close to nature in a stand-alone location or on the fringe of the settlement as a risk factor for disease in multivariable analysis with an adjusted OR of 10.8 (95% CI 1.3–89.0). Other variables including keeping cats were not associated with disease. Targeted prevention, future post-exposure-prophylaxis, and timely diagnosis remain challenging.